Does viscosity drive the dynamics in an alcohol-based deep eutectic solvent? - Chatterjee, Srijan; Deshmukh, Samadhan H.; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Deep eutectic solvents, consisting of heterogeneous nano-domains of hydrogen-bonded networks, have evolved into a range of viscous fluids that find applications in several fields. As viscosity is known to influence the dynamics of other neoteric solvents like ionic liquids, understanding the effect of viscosity on deep eutectic solvents is crucial to realize their full potential. Herein, we combine polarization-selective pump-probe spectroscopy, two-dimensional infrared spectroscopy, and molecular dynamics simulations to elucidate the impact of viscosity on the dynamics of an alcohol-based deep eutectic solvent, ethaline. We compare the solvent fluctuation and solute reorientation time scales in ethaline with those in ethylene glycol, an ethaline constituent. Interestingly, we find that the solute's reorientation apparently scales the bulk viscosity of the solvent, but the same is not valid for the overall solvation dynamics. Using the variations in the estimated intercomponent hydrogen bond lifetimes, we show that a dissolved solute does not sense the bulk viscosity of the deep eutectic solvent; instead, it senses domain-specific local viscosity determined by the making and breaking of the hydrogen bond network. Our results indicate that understanding the domain-specific local environment experienced by the dissolved solute is of utmost importance in deep eutectic solvents.

Does variation in composition affect dynamics when approaching the eutectic composition? - Chatterjee, Srijan; Chowdhury, Tubai; Bagchi, Sayan (Journal of Chemical Physics, 2023)
Deep eutectic solvent is a mixture of two or more components, mixed in a certain molar ratio, such that the mixture melts at a temperature lower than individual substances. In this work, we have used a combination of ultrafast vibrational spectroscopy and molecular dynamics simulations to investigate the microscopic structure and dynamics of a deep eutectic solvent (1:2 choline chloride: ethylene glycol) at and around the eutectic composition. In particular, we have compared the spectral diffusion and orientational relaxation dynamics of these systems with varying compositions. Our results show that although the time-averaged solvent structures around a dissolved solute are comparable across compositions, both the solvent fluctuations and solute reorientation dynamics show distinct differences. We show that these subtle changes in solute and solvent dynamics with changing compositions arise from the variations in the fluctuations of the different intercomponent hydrogen bonds.